AHEAD 3‐45 study design: A global study to evaluate the efficacy and safety of treatment with BAN2401 for 216 weeks in preclinical Alzheimer's disease with intermediate amyloid (A3 trial) and elevated amyloid (A45 trial): Clinical trial design and implementation. (7th December 2020) - Aisen, Paul S.; Zhou, Jin; Irizarry, Michael C.; Kramer, Lynn D; Swanson, Chad J.; Dhadda, Shobha; Rabe, Martin; Krause, Stephen; Li, David JianJun; Raman, Rema; Donohue, Michael C.; Sethuraman, Gopalan; et al.
Abstract: Background: Aβ pathologies occur years prior to cortical tauopathy, neurodegeneration, and clinical symptoms. BAN2401 is a humanized immunoglobulin G1 monoclonal antibody that selectively binds to soluble Aβ aggregated species (oligomers, protofibrils). BAN2401 reduced amyloid on PET and slowed cognitive decline in a Phase 2 study in early symptomatic AD. The AHEAD 3‐45 study will test the safety and efficacy of BAN2401 even earlier in the AD continuum. Method: AHEAD 3‐45 consists of two trials (A3 Trial and A45 Trial) under a single protocol and screening process, common schedule of assessments, and distinct dosing regimens tailored to the baseline amyloid level. The study is a Public‐Private Partnership of the Alzheimer's Clinical Trial Consortium (ACTC), National Institutes of Health (NIH), and Eisai, Inc. The A3 Trial will enroll cognitively normal individuals (CN) with intermediate amyloid (approximately 20‐40 centiloids), at risk for further amyloid accumulation and development of neurofibrillary tangles on tau PET over four years. Approximately 400 participants will be randomized 1:1 to placebo or BAN2401 infusion—8 weeks of titration followed by 10 mg/kg every four weeks for 216 weeks. The A45 Trial will enroll CN individuals with elevated amyloid, defined as amyloid PET approximately >40 centiloids, at risk for cognitive decline over four years. Approximately 1000 participants will be randomized 1:1 to placebo or BAN2401 infusion—8 weeks of biweekly titration dosing, then 10 mg/kg biweekly induction dosing through 96 weeks to clear aggregated Ab, followed by 10 mg/kg every four weeks maintenance dosing through 216 weeks to prevent reaccumulation of Aβ. Result: Longitudinal cognitive, safety, amyloid and tau PET, MRI and fluid biomarker assessments will be performed. The primary outcome of the A3 Trial is prevention of brain amyloid accumulation by amyloid PET at 216 weeks, with delay of tau PET accumulation as a key secondary outcome. The primary outcome measure of the A45 Trial is the Preclinical Alzheimer's Disease Cognitive Composite 5 (PACC5) scale at 216 weeks. Conclusion: The AHEAD 3‐45 Study will test whether BAN2401 can prevent the accumulation and spread of Aβ deposition, downstream tau pathology, and cognitive decline in at‐risk cognitively normal individuals prior to significant irreversible neurodegeneration.